MORPHOLOGICAL CONTEXTUALIZATION OF CAÑARI FAMILY NAMES IN THE SOUTHERN ANDES OF ECUADOR - Cabrera Moreno, Sandra Leonor (Universidad-Verdad, 2025)
Before the arrival of the Incas in the 15th century, the Cañari people were mainly located in the territories that nowadays are the provinces of Azuay and Cañar in the Southern Andes of Ecuador. The city of Cuenca, capital of the province of Azuay, was known as Guapdondélic, which literally means “plain as big as the sky” in Cañari, a language that is extinct today, but whose legacy has survived in the anthroponyms and toponyms of the region. Despite the extinction of the Cañari language, family names in Cuenca are vivid markers of the Cañari heritage. Then, bearing in mind the dynamic nature of language contact and morphological borrowing, it is not surprising that the Cañari anthroponyms still existing in the region show not only Cañari morphemes but a combination of both Kichwa roots and Cañari affixes. Consequently, to unveil this Cañari heritage, the present study discusses the affixation of a total of fifty-six Cañari family names, contextualizing such morphological analysis in its historical and toponymical settings through the triangulation of validated document sources.